What great salespeople do : the science of selling through emotional connection and the power of story - Bosworth, Michael T.; Zoldan, Ben (McGraw Hill-Ascent Audio, 2012)
This groundbreaking book offers extraordinary insight into the greatest mystery in sales: how the very best salespeople consistently and successfully influence change in others, inspiring their customers to say yes. Top-performing salespeople have always had a knack for forging connections and building relationships with buyers. Until now, this has been considered an innate talent. What Great Salespeople Do challenges some of the most widely accepted paradigms in selling in order to prove that influencing change in buyers is a skill that anyone can learn. The creator of Solution Selling and CustomerCentric Selling, Michael Bosworth, along with veteran sales executive Ben Zoldan, synthesize discoveries in neuroscience, psychology, sociology, anthropology, and other disciplines, combining it all into a field-tested framework-helping you break down barriers, build trust, forge meaningful relationships, and win more customers. This book teaches you how to: Relax a buyer's skepticism while activating the part of his or her brain where trust is formed and connections are forged Use the power of story to influence buyers to change Make your ideas, beliefs, and experiences "storiable" using a proven story structure Build a personal inventory of stories to use throughout your sales cycle Tell your stories with authenticity and real passion Use empathic listening to get others to reveal themselves Incorporate storytelling and empathic listening to achieve collaborative conversations with buyers Breakthroughs in neuroscience have determined that people don't make decisions solely on the basis of logic; in fact, emotions play the dominant role in most decision-making processes. What Great Salespeople Do gives you the tools and techniques to influence change and win more sales.